EDUKASI KESEHATAN DAN KESELAMATAN KERJA PADA NELAYAN - Pati, Diva Diah; Asmin, Elpira; Awan, Razana; Titaley, Christiana R.; Tobing, Rezki Toding Allo; Bugis, Riansyah; Oei, Marcietta; Hetharie, Yitkel; Amanupunjjo, Graily; Gofu, Neils (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
Fishermen are one of the communities in the waters that need attention from the government in terms of health. Ignoring the safety of fishermen will have an impact on increasing expenditure in the economic sector because there are medical costs that must be borne and also have an effect on the environment. Therefore, it is necessary to increase education related to health and the benefits of working safety equipment for fishermen. This educational activity was carried out by distributing leaflets and outreach to the homes and fishermen's bases of Negeri Hitumessing, Leihittu District, Central Maluku Regency. There were 21 respondents; only 4 fishermen had swimming floats, only around 19%, and only 2 had swimming goggles, or around 10% of the total respondents. Not all fishermen also have fishing boats, or the local people call them babongs. Only about 38% or 7 fishermen own a boat. Only 1 or 5% of the ships have goggles; similarly, only 1 has a life jacket. The results of community service activities are expected so that fishermen can understand occupational health and safety, its impact, and the importance of occupational health and safety.